Transformational Leadership and Teacher Performance Enhancement in the Merdeka Curriculum Context - M Murniati; Ahmad Rifandi (Journal of Science and Education (JSE), 2025)
This study aims to analyze the implementation of transformational leadership among school principals in enhancing teacher performance within the context of the Kurikulum Merdeka (Independent Curriculum). A qualitative approach with a comparative case study design was employed, involving two senior high schools in West Bandung Regency: SMAN 1 Padalarang, a National Adiwiyata School, and SMAN 1 Lembang, one of the first-generation Sekolah Penggerak (Driving Schools). Data were collected through in-depth interviews, observations, and document analysis, and analyzed using Miles and Huberman’s interactive model with source triangulation and member checking to ensure validity. The findings reveal that principals demonstrating transformational leadership successfully motivate teachers to innovate, strengthen collaboration, and improve teaching performance. The four dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration contributed significantly to fostering teacher performance and building a school culture adaptive to the demands of the Kurikulum Merdeka. The novelty of this study lies in its contextual analysis of how transformational leadership principles are adapted and applied in schools with distinct characteristics. The findings underscore that the success of the Kurikulum Merdeka implementation largely depends on the principal’s ability to translate transformational values into inspirational, collaborative, and empowering leadership practices.